2021
DOI: 10.3126/janr.v4i1.33281
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of white grain maize varieties for growth, yield and yield components

Abstract: Maize (Zea mays L.)  is one of the most commonly cultivated crop after rice in Nepal. The present study was done to evaluate and recommend the best performing white maize genotypes in mid hill region of Nepal. This study was conducted at research field of Kavre, Nepal during the rainy season of 2019. Five white maize genotypes were evaluated in randomized complete block design with four replications where Deuti used as standard check. Ear and plant height of plant, days to 50% silking and tasseling, count of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…KWM-92 × KWM-93 (9.83 t ha -1 ) yielded significantly more grain than KWM-91 × KWM-93 (9.50 t ha -1 ) under the Khumaltar conditions. These findings were similar to those of Kafle et al (2020), Shrestha (2016), Shrestha et al (2019), Adhikari et al (2018), Bastola et al (2021), Dhakal et al (2018), and Prasai et al (2015), who observed significant differences in grain yield between maize genotypes. The genetic makeup of maize genotypes differed, resulting in differences in grain yield across the locations.…”
Section: Resultssupporting
confidence: 89%
“…KWM-92 × KWM-93 (9.83 t ha -1 ) yielded significantly more grain than KWM-91 × KWM-93 (9.50 t ha -1 ) under the Khumaltar conditions. These findings were similar to those of Kafle et al (2020), Shrestha (2016), Shrestha et al (2019), Adhikari et al (2018), Bastola et al (2021), Dhakal et al (2018), and Prasai et al (2015), who observed significant differences in grain yield between maize genotypes. The genetic makeup of maize genotypes differed, resulting in differences in grain yield across the locations.…”
Section: Resultssupporting
confidence: 89%
“…Rampur composite had cob with lowest diameter than other genotypes which might be the reason for lower yield of maize. Maruthi and Rani (2015) and Bastola et al (2021) also had similar results in cob diameter among different maize genotypes. Cob length-diameter ratio was more in Rajkumar while CP-858 had lowest length diameter ratio.…”
Section: Number Of Leaf and Stalk Lodging Of Maizesupporting
confidence: 60%
“…Due to lowest number of kernel per rows in Rampur composite lower yield was recorded. Bastola et al (2021) and Singh et al (2013) also reported varietal differences in number of kernels per row. JKMH 502 had more weight of thousand kernels while lowest was observed in CP-666 than other genotypes in research.…”
Section: Number Of Leaf and Stalk Lodging Of Maizementioning
confidence: 93%
“…Plant height is important traits for determining the lodging and grain yield of maize. Lower the plant height fosters less accumulation of photosynthate in the maize stover and play the vital role for translocation of produced photosynthate to the grain and gives the higher yield (Bastola et al 2021). Similarly, varieties had highly significant effect on days to 50% tasseling but there is no any significant effect on days to silking (Table 1).…”
Section: Plant and Ear Height Flowering And Number Of Leaf Below And Above Main Cobmentioning
confidence: 98%
“…Akbar et al (2008) and Kandel et al (2017) also reported significant variation for days to silking among different maize hybrids. Due to earlier tasselling and silking, less number of days will be available for the crop growth by which less photosynthate will deposit in the grain and affect the grain yield which might be the reason for higher yield in the CP-666 and lower yield in TX-369 (Bastola et al 2021).…”
Section: Plant and Ear Height Flowering And Number Of Leaf Below And Above Main Cobmentioning
confidence: 99%